PENINGKATAN KEMAMPUAN MENULIS PENGALAMAN MELALUI METODE PEMBERIAN TUGAS SISWA KELAS V SD NEGERI 001 PAGARAN TAPAH DARUSSALAM - Hasanah ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the lack of writing skills students of class V SDN 001 PagaranTapah Darussalam. This study aims to improve the ability of writing experience fifth gradestudents at SDN 001 Pagaran Tapah Darussalam with the method of assignment, which iscarried out for 1 month. The subjects were fifth grade students at SDN 001 Pagaran TapahDarussalam totaling 33 people consisting of 15 men and 18 women. Form of research isclassroom action research. The research instrument consists of instruments and instrumentperformance data collection activity observation sheet form teacher and student activity. Basedon the results of the study revealed that the method of administration tasks can improve theability of fifth grade students at SDN 001 Pagaran Tapah Darussalam writing experience. It isknown from (a) the activities of teachers has increased in the first cycle obtain a percentage of74.3% (Good) and the second cycle gained 82.9% (Very Good). In addition the student activityalso increased in the first cycle obtained 71 , 1% (Good) and the second cycle cycle obtain apercentage of 75.8% (Good); and (b) increased learning outcomes in basic score average valueincreased 64.4 students in the first cycle students' average score of 70.9 and the second cycle ofthe average value of 85 students.